Study the Microwave absorption characteristics of U-type barium hexaferrites prepared using chemical method (Journal of the College of Basic Education, 2022)
U-type Barium hexaferrite with stoichiometric composition Ba 4 Co 0.3 Zn 0.6 Cu 1.1 Fe 36 O 60 has been prepared using citrate precursor method atlow temperatures (1000, 1050, and 1100°C). The XRD patterns of the preparedpowders at temperatures (1000 and 1050°C) show the presence of spinel, M andY-type phases, while U-type ferrite phase(with crystallite size 40 – 90 nm)obtained at 1100 °C. Radar absorbing nanocomposite samples were prepared bymixing, molding and curing mixtures of Ba 4 Co 0.3 Zn 0.6 Cu 1.1 Fe 36 O 60 powders(prepared at 1100°C) with epoxy resin (ER),(80:20% weights).The microwaveattenuation measurements were based on the Transmission/Reflection methodusing rectangular waveguides as the confining medium for the samples at 8.0 – 12GHz frequencies.